Disasters and Cultural Heritage: planning for prevention, emergency management and risk reduction. Issue 1 (November 2020) - Grazia De Paoli, Rosa; Di Miceli, Enrica; Giuliani, Francesca
Abstract: The need to investigate the topic of risk management of cultural heritage and to work on the regulatory framework relating to its protection and enhancement become even more urgent in light of the recent seismic events that hit the Italian territory. The current emergency planning methods against natural or human-induced hazards have proven to be deficient. Reflecting on the way we normally conceive the cultural assets, the question is not only how to protect our heritage, but how to shift our perception to conceive it as a positive asset, and not only a responsibility. Cultural heritage is not only a document of the identity of a community and a territory, but it can also be the keystone for reconstruction and building resilience to disasters. Starting from this awareness, this paper introduces a methodology for the analysis heritage sites aiming at proposing risk reduction strategies that consider the participatory dialogue between different professional figures. The approach is based on the consolidated methodological framework identified by UNESCO, ICCROM and ICOMOS. The study entails a preliminary evaluation of the most hazardous events, threats and risks that can impact on the heritage values. By considering a worst-case scenario, the procedure allows for modelling and stressing the post-event resilience of the site or cultural asset under consideration. The results of the investigation highlight the potential of this procedure in practical terms. In fact, its adaptability to different scales and contexts responds to the common need of a rapid, integrated methodology for risk assessment. Finally, the paper discusses the current prevention policies involving cultural heritage, focusing on the need to balance conservation and active protection issues to those of safety.